Pengembangan E-Learning Materi Hukum Newton Untuk Mengembangkan Keterampilan Berpikir Kritis Siswa Sekolah Menengah Atas - Septania Pratiwi; Ketang Wiyono; Zulherman Zulherman (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The study aims to produce the e-learning physics of Newton's legal material to develop the critical thinking skills of high school students who have higher and practical validity rates. The model of development research used is Rowntree models. The evaluation phase used is Tessmer's formative evaluation consisting of four phases: Self evaluation, expert review, one-to-one evaluation, and small group evaluation. Data collection techniques using walkthroughs and polls. This level of e-learning validity is judged by three experts, namely in material aspects, learning design aspects, and e-learning aspects as well as data analysis using the Aiken V Index to determine the consensus of the experts. The results of the development of e-learning indicate that the resulting media is suitable for use in learning physics. This can be seen from the Aiken V index value of 0.94 with a high level of validity category. Meanwhile, one-to-one evaluation and small group evaluation are obtained by average result of 81.84% and 90.00% and also includes very practical category.